The Causes of Bureaucratic Petty Corruption in the Province of Aceh in Indonesia - Muhammad Bin Abubakar (Master Program of Sociology, Universitas Malikussaleh, 2021)
This article tried to explain the causes of petty corruption in the Province of Aceh. It took the kleptocratic approach and Patrimonialism Politics model in explaining the causes of corruption in the region. It had utilized extensively the secondary sources data from books, journal articles and local media report. It found that after the end of the conflict, Aceh was captured by the local kleptocratic elite and they have been effectively used the patrimonialism politics in maintaining their hegemony and protect their group interest. Leaving the region as the state of being one of the poorest region in Indonesia.